„…az élet értékességének kérdésében a jog nem ítélhet”: Az emberi élet védelme Angyal Pál vonatkozó műveiben - Lehotay, Veronika; Pauló, Tamás Mihály (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The aim of this study is to present and interpret the criminal law thinking of Pál Angyal from both historical and theoretical perspectives, with particular emphasis on the issue of the protection of life. As a prominent figure in early 20th-century Hungarian legal scholarship, Angyal examined numerous aspects of the criminal law protection of human life, including homicide, infanticide, participation in suicide, and euthanasia. At the core of his approach lies the inalienability of the right to life and the state’s duty to protect it – principles that remain relevant today. The right to life, as reflected in Angyal’s works, is closely intertwined with the dilemma between law and morality, a tension that is also addressed in this study.